Ethics education and accountants' moral character development in Nigeria: an evaluation of Rest's hypotheses. (24th November 2021) - Okpala, Kenneth Enoch; Mlanga, Sunday
This study evaluated the effect of accounting ethics education on the accountants' moral character development using the James Rest model of 1983. The research concentrated on teaching ethics courses to accounting in Nigeria. A cross sectional survey research design was applied. Four hundred one participants were the sample population with 270 valid responses returned and analysed. The regression method was employed to test the formulated null hypotheses. The study found that accounting ethics education has a positive and significant effect on the accountants' moral character development. It was concluded that teaching ethics courses to accounting students would aid the development of accountants' moral character and moderate corporate failure. Studies conducted in this area fail to consider ethics and the development of the accountant's moral character using Rest's hypotheses in Nigeria. The omission created gaps in the literature and left the relationship between the variables inconclusive. The current study has explored the relationship between the variables.